(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The Assurance Services Are Represented By Expressing A Clear And Independent Opinion On All Financial And Non-Financial Information, As It Is Broader Than The Services Related To Auditing Financial Statements And Expressing Opinion (Certification) And Extends Them To A Wider Range, And It Is Possible To Distinguish Between Auditing And Certification Services And Confirming That Audit Services Relate To Expressing Opinion On Financial Statements And Certification Services Related To By Expressing An Opinion On A Wide Range Of Financial Information And More Broadly Than The Financial Statements And Assurance Services That Include Expressing An Opinion On Integrated Financial And Non-Financial Information And From This Standpoint Came The Idea Of ​​The Research Tagged "Enhancing Auditor Reporting In Light Of International Assurance Standards And Their Reflection On Activating The Credibility Of Sustainability Reports" The Research Problem Was Represented By One Question, Which Is That “International Assurance Standards Have An Effective Role In Strengthening Auditor Reporting And Activating The Credibility Of Sustainability Reports.” The Aim Of The Research Is To Clarify The Concept Of Auditor Reporting And The Role Of International Assurance Standards In Developing And Strengthening It, As Well As The Role Of International Assurance Standards In Enhancing The Credibility Of Sustainability Reports. The Research Reached Several Conclusions, The Most Important Of Which Is The Existence Of A Great Desire On The Part Of Auditors To Develop Their Professional Capabilities And Shift From Traditional Auditing To Auditing And Examination And Providing Assurance Services In Accordance With International Standards. The Research Also Reached Several Recommendations, The Most Important Of Which Is That Audit Organizations And Bodies Should Focus On Developing Their Cadres In Terms Of Courses. Conferences and Workshops in the Field Of Assurance Services In Accordance With “International Assurance Standards.”